AN ANALYSIS OF DEIXIS ON THE CHARACTERS IN BRAVE MOVIE - Yasinta Trililis Anjelina Maduwu; Rahmaditya Khadifa Abdul Rozzaq Wijaya (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2024)
Deixis refers to the need for contextual information to understand certain words and phrases in an utterance. This research aims to analyze the types and functions of deixis in the movie Brave by using a qualitative descriptive approach. Data collection is done by watching the movie, reading the transcript, and categorizing the dialogue based on the type of deixis by using Levinsons method. Through dialog and gesture analysis, this study highlights how deixis is used strategically in the movie Brave to connect the storyline and guide the audience's interpretation. The findings are compared with previous research on deixis in song lyrics, newspapers and other movies, illustrating similarities and unique aspects in the context of Brave. This research emphasizes the role of deixis in enhancing narrative coherence and audience engagement, positioning it as an important tool in film analysis and storytelling. The research categorizes 60 instances of deixis into five types-person, time, place, discourse, and social deixis-with personal deixis identified as the most common among them.